ANALISIS POHON KEPUTUSAN TERHADAP ANALOGI TAKSONOMI BLOOM UNTUK MENENTUKAN TINGKAT KEMAMPUAN MAHASISWA - Danny Kriestanto (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2016)
People’s learning ability are varies, including for the undergraduate students. These students have different capability in absorbing knowledge, as previous researches stated (2010-2015). In this research, the data that had been used were twice more than the previous research. In order to find more information about Cognitive Aspects that had been affecting STMIK AKAKOM students in using Information Technology, decision tree were used. The result shown that generally the students are divided into 2 massive groups: a group that learn to memorize by applying first, and a group that learn creating by applying before learn how to memorize and understand how things work. That is, however, showing the learning pattern of the students.